2020
DOI: 10.1097/aco.0000000000000812
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative neurocognitive disorders

Abstract: Purpose of review Alterations in cognitive functions are common in the perioperative course. Although often unnoticed by physicians, these alterations might have distinct long-term consequences for the patient with regard to everyday functioning, self-dependency, and quality of life. In recent years, however, perioperative cognition has gained increased interest, both by clinicians and scientists, and knowledge of the preventive measures of postoperative cognitive decline has become mandatory for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 75 publications
1
64
1
1
Order By: Relevance
“…First, we will only enrol patients admitted to the ICU, which may represent a population at high risk of POD. [3][4][5] Thus, our results may be limited for generalising to the entire population of patients undergoing intracranial surgery. Second, we only evaluate early outcomes up to 28 days after the operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we will only enrol patients admitted to the ICU, which may represent a population at high risk of POD. [3][4][5] Thus, our results may be limited for generalising to the entire population of patients undergoing intracranial surgery. Second, we only evaluate early outcomes up to 28 days after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…1 2 Studies have shown that POD is associated with adverse outcomes, including prolonged length of stay in the ICU and hospital, higher morbidity and mortality risks, increased healthcare costs, and reduced long-term quality of life. [3][4][5] However, patients with neurological illness are usually excluded from previous researches, and delirium is underestimated due to potential consciousness and cognition impairment. 6 7 Recently, more attention has been devoted to POD in patients after neurosurgery.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Hayashi et al reported that a lower preoperative exercise capacity, assessed by the 6-minute-walking distance in patients undergoing cardiac surgery was associated with an increased incidence of PNCD [ 71 ]. However, their study assessed cognitive function only 14 days after surgery using the mini mental state examination, which is a sub-optimal tool for detecting PNCD due to both floor- and ceiling-effects, and poor sensitivity for detecting mild or medium cognitive impairment [ 72 , 73 ]. Furthermore, a decline in cognitive performance at 14 days after surgery is not necessarily caused by persistent neurocognitive disorder, as this is also likely to be related to delirium or delayed cognitive recovery caused by pain, residual drug effects, limited mobility, and fatigue [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that the occurrence of POD is attributable to a complex interaction among many perioperative factors. 2 In this study, we noticed that when multivariate logistic regression analysis was used for identification of potential risk factors for POD, the authors only include the preoperative factors in the model, but did not take intraoperative and postoperative factors into the model. The available evidence shows that type of surgery, intraoperative hypotension and hypoxemia, long duration of surgery and large volume of intraoperative transfusions are independent risk factors for POD in elderly patients undergoing hip surgery.…”
Section: The Use Of Preoperative Prognostic Nutritional Index and Agementioning
confidence: 99%